3D-Representations for studying deep-sea coral habitats in the Lacaze-Duthiers Canyon, from geological settings to individual specimens. (September 2022) - Fabri, Marie-Claire; Dugornay, Olivier; de la Bernardie, Xavier; Guerin, Charline; Sanchez, Pierre; Arnaubec, Aurelien; Autin, Tim; Piasco, Romain; Puig, Pere
Abstract: The Lacaze-Duthiers Canyon is located in the western Mediterranean Sea and is long known for hosting cold-water coral colonies in the canyon head region at depths ranging from 250 to 550 m. In 2019 during the CALADU cruise, three kinds of 3D-reconstructions were applied to better understand the distribution of coral colonies, their habitat and their skeleton morphologies. The canyon's flanks were mapped using a hull-mounted echosounder and an ROV multibeam echosounder. Digital terrain models were built with resolutions of 5 and 1 m and examined in three dimensions. ROV bathymetric data collected on the canyon's flanks made it possible to highlight a series of sub-parallel structures identified as lithified sedimentary strata along which coral colonies grow. Coral assemblages were explored at four locations and photographic images were assembled using structure from motion techniques to build photogrammetric models. Coral assemblages reconstructed in 3D enabled geo-localizing and recreating coral colonies on 16 models over a total area of 4370 m 2 . Two colonial species, Madrepora oculata and Desmophyllum pertusum were plotted and reported on bathymetric models to interpret their location at the scale of the canyon. The coordinates and depth of the colonies were used to calculate the vertical distribution (limited to our small bathymetric exploration, between 339 and 214 m depth) and density of populations (up to 4.3 colonies per m 2 ). The spatial coverage of the 16 assemblages measured between 100 and 600 m 2 each. The sizes of the colonies were measured to analyze the population structures of both species (mean sizes of 28 cm for D. pertusum and 18 cm for M. oculata, maximum sizes 1 m and 0.5 m, respectively, bushes 2.5 m long). In addition, lost fishing gears were quantified, longlines measured and their densities calculated (0.16 m/m 2, up to 0.30 m/m 2 ). An area with exuberant orange colonies of D. pertusum was discovered for the first time in the Lacaze-Duthiers Canyon. Five deep-sea scleractinian species were collected and micro-tomographic scans computed to view their intrinsic skeleton organization. Micro-CT scans of M. oculata, D. pertusum, Desmophyllum dianthus, Caryophyllia smithii, and Dendrophyllia cornigera enabled longitudinal and transversal cuts, highlighting morphological criteria for species identification and the multidirectional examination of specimens. We observed a thin canal connecting calices along the axis of D. pertusum colonies, and separate calices along the axis of M. oculata colonies. Highlights: Canyon walls were mapped with a MBES installed with a 45° angle. A surface of 4370 m 2 was reconstructed on Cold-Water Corals ecosystem. The highest density of coral colonies among the Mediterranean canyons. Coral colonies faced prevailing currents coming from canyon head incisions. A thin canal connects buds of successive generation in Desmophyllum pertusum .